The Rohingya in Myanmar between displacement and genocide : a religious war of Buddhism against Islam? : a conflict analysis - Waals, Peter von de (Las Vegas, USA : [Place not Identify], 2022)
The world public reacted shocked when a mass flight of the Rohingya from Burma to Bangladesh took place at the end of 2017. This conflict, which took place in a region that normally attracts little attention in the German media, was thus put in the spotlight of the media. Apparently, this conflict seemed to have a religious component. Therefore, this paper will address the question of whether this conflict was a Buddhist religious war against the Muslim Rohingya. To this end, the conflict content of religion will first be analysed in the article "Religions in Conflicts - Religious Faith as Source of Violence and Peace" by Rittberger/Hasenclever. In addition, the conflict model they have developed will be used as the basis for the analysis of the facts. Afterwards, a short historical review of the historical roots of the ethnic conflicts within Burma will be given. To this end, history will begin shortly before the British colonised the country. Then, the relationship between Muslims and the Burmese Buddhist majority population will be outlined. It is to be analyzed, which measures were undertaken by the government against the Muslims, and which social climate prevails against the Muslims.Based on this, the difficult relationship to the Rohingya will be outlined and the course of the conflict will be discussed.Finally, the conflict will be classified on the basis of the Rittberger/Hasenclever conflict model.A conclusion concludes the work.
Includes bibliographical references.
Refugee studies unit (RSU), CPJ.
Development Book Agency
Keywords: Rohingya (Burmese people).; Genocide; Rohingya (Burmese people) -- Bangladesh; Refugees -- Burma